2015
DOI: 10.1080/10408398.2015.1040487
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Fruits and Vegetables and Cardiovascular Diseases Risk

Abstract: Diet is likely to be an important determinant of cardiovascular disease (CVD) risk. In this article, we will review the evidence linking the consumption of fruit and vegetables and CVD risk.Efforts were initially focused on individual protective nutrients, such as vitamin E, vitamin C, and β-carotene, in an attempt to identify putative intervention strategies.However these have generally proven to be disappointing when tested in clinical trials.The evidence now suggests that a complicated set of several nutrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
142
0
18

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 201 publications
(189 citation statements)
references
References 146 publications
4
142
0
18
Order By: Relevance
“…Many meta‐analyses have found that the intake of vegetables and fruit is inversely associated with the risk of weight gain, CVD, and type 2 diabetes . Nevertheless, the intake vegetables and fruit remains low worldwide . Therefore, nutritional education and health policies are needed to promote the intake of vegetables and fruit to decrease the burden of CMDs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many meta‐analyses have found that the intake of vegetables and fruit is inversely associated with the risk of weight gain, CVD, and type 2 diabetes . Nevertheless, the intake vegetables and fruit remains low worldwide . Therefore, nutritional education and health policies are needed to promote the intake of vegetables and fruit to decrease the burden of CMDs.…”
Section: Discussionmentioning
confidence: 99%
“…37 Nevertheless, the intake vegetables and fruit remains low worldwide. 38 Therefore, nutritional education and health policies are needed to promote the intake of vegetables and fruit to decrease the burden of CMDs.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological evidence suggests that a diet rich in fruit and vegetables prevents or may delay the onset of various diseases such as cardiovascular diseases, cancer, diabetes, and dementia (Alissa and Ferns, 2015). These effects have been attributed, in part, to plant-derived poly-phenolic compounds that are good inducers of anti-inflammatory pathways 3), each bar is reported as the intensity of optical density (IOD) AE SD.…”
Section: Discussionmentioning
confidence: 99%
“…Endogenous metabolic pathways and exogenous factors, including nutrient molecules originating from diet, affect most cellular processes, considerably influencing human health state and susceptibility to diseases development. In particular, dietary intake, besides reintegrating metabolic balance, provides bioactive molecules that are selectively able to modulate molecular mechanisms involved in the etiology of numerous pathological conditions, especially cardiovascular and neoplastic diseases (Alissa & Ferns, ; Maehre, Jensen, Elvevoll, & Eilertsen, ; Song, Garrett, & Chan, ). Numerous bioactive nutrients are being progressively identified and their chemopreventive effects are being described at clinical and molecular mechanism levels, revealing the ability of some of them to regulate gene expression.…”
Section: Introductionmentioning
confidence: 99%
“…of numerous pathological conditions, especially cardiovascular and neoplastic diseases (Alissa & Ferns, 2017;Maehre, Jensen, Elvevoll, & Eilertsen, 2015;Song, Garrett, & Chan, 2015). Numerous bioactive nutrients are being progressively identified and their chemopreventive effects are being described at clinical and molecular mechanism levels, revealing the ability of some of them to regulate gene expression.…”
mentioning
confidence: 99%